PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS SAINTFIK PADA MATERI ATURAN DAN NORMA DI KELAS IV SEKOLAH DASAR - Kurnia Marifatul Latifah; Otib Satibi Hidayat; M. Syarif Sumantri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to develop and produce a product in the form of scientifically based interactive multimedia to support the learning of Pancasila Education regarding rules and norms for class IV elementary schools and to determine the feasibility of the product that has been developed. The research was carried out at Gunung Putri Elementary School with a total of 33 respondents, class IV elementary school students. The method used in this research is Research and Development (R & D) with a 4D development model, namely Defune, Design, Develop, and Dessiminate. However, this research was carried out only up to the third stage. Data collection techniques use observation, interviews and questionnaires. This research produces a product in the form of a scientifically based interactive multimedia application. The development of scientifically based interactive multimedia products received evaluations carried out by expert reviews, namely media experts, language experts and material experts. The results of the validation assessment from media experts obtained a feasibility percentage of 96.4% in the very good category. The results of the validation assessment from language experts obtained a feasibility percentage of 97.5% with a very good category. The assessment results from material experts were based on obtaining a percentage of 90.9% in the very good category. The results of the one-to-one trial obtained feasibility of 89.6% in the very good category. The results of the small group trial obtained feasibility of 93.5% in the very good category. The results of the field test obtained a feasibility of 92.1% in the very good category. Thus, the objectives of this research and development have been achieved and are suitable for use by fourth grade elementary school students. Keywords: Ineractive Multimedia, Scientific Based, Pancasila Education Learning